Targeted Deletion of Loxl3 by Col2a1-Cre Leads to Progressive Hearing Loss - Liu, Ziyi; Bai, Xinfeng; Wan, Peifeng; Mo, Fan; Chen, Ge; Zhang, Jian; Gao, Jiangang (Frontiers in Cell and Developmental Biology, 2021)
Collagens are major constituents of the extracellular matrix (ECM) that play an essential role in the structure of the inner ear and provide elasticity and rigidity when the signals of sound are received and transformed into electrical signals. LOXL3 is a member of the lysyl oxidase (LOX) family that are copper-dependent amine oxidases, generating covalent cross-links to stabilize polymeric elastin and collagen fibers in the ECM. Biallelic missense variant of LOXL3 was found in Stickler syndrome with mild conductive hearing loss. However, available information regarding the specific roles of LOXL3 in auditory function is limited. In this study, we showed that the Col2a1-Cre-mediated ablation of Loxl3 in the inner ear can cause progressive hearing loss and degeneration of outer hair cells and spiral ganglion neurons. The abnormal distribution of collagen II in the spiral ligament and increased inflammatory responses were also found in Loxl3col2/col2 mice. Amino oxidase activity exerts an effect on collagen; thus, Loxl3 deficiency was expected to result in the instability of collagen in the spiral ligament and the basilar membrane, which may interfere with the mechanical properties of the organ of Corti and induce the inflammatory responses that are responsible for the hearing loss. Overall, our findings suggest that Loxl3 may play an essential role in maintaining hearing function.